2015
DOI: 10.1002/tal.1270
|View full text |Cite
|
Sign up to set email alerts
|

Forward directivity near-fault and far-fault ground motion effects on the behavior of reinforced concrete wall tall buildings with one and more plastic hinges

Abstract: SUMMARYNear-fault (NF) ground motion having forward directivity and far-fault (FF) earthquakes can generate different responses on tall reinforced concrete cantilever walls. In this paper, the behavior of the core wall buildings were examined by performing nonlinear time history analyses on 20-story, 30-story and 40-story fiber element models. The concept of one, two, three and extended plastic hinge in the core walls subjected to the NF motions having forward directivity (pulse-like) and FF motion was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…It is worth noting that the other responses of the core‐wall buildings have been studied in another paper (Beiraghi et al, ). With the 1PH approach, the moment demand around the mid‐height of the core wall may exceed the moment demand at the base region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the other responses of the core‐wall buildings have been studied in another paper (Beiraghi et al, ). With the 1PH approach, the moment demand around the mid‐height of the core wall may exceed the moment demand at the base region.…”
Section: Discussionmentioning
confidence: 99%
“…Figure shows the general view of the models. More information on designed buildings could be found elsewhere (Beiraghi et al, ).…”
Section: Rc Core‐wall Designmentioning
confidence: 99%
“…Commonly, in the RSA procedure, modal responses are reduced by an identical R factor for all modes. Several researchers have demonstrated that the formation of plastic hinges at the base of the cantilever walls essentially reduces response of the first vibration mode, while higher vibration modes are not reduced to the same degree as the first mode (Beiraghi et al ., ). Therefore, the conventional RSA procedure is not an appropriate approach for designing of cantilever walls with plasticity at the base (Priestley et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…These ground motions, called pulse-like ground motions, have been identi ed as the cause of severe demands in structures, which can exceed the expected demands typically resulting from Response Spectrum Analysis (RSA) procedure [26][27][28][29][30]. Many studies have demonstrated that buildings located in an NF zone undergo highly inelastic responses caused by velocity pulses in the fault normal component of some seismic ground motions [31][32][33].…”
Section: Introductionmentioning
confidence: 99%